The Importance of Well-Being on Resiliency of Filipino Adults During the COVID-19 Enhanced Community Quarantine: A Necessary Condition Analysis - Camitan, Desiderio S.; Bajin, Lalaine N. (Frontiers in Psychology, 2021)
Nation-wide community quarantines and social distancing are part of the new normal as results of the global COVID-19 pandemic. Since extensive and prolonged lockdowns are relatively novel experiences, not much is known about the wellbeing of individuals in such extreme situations. This research effort investigated the relationship between wellbeing elements and resiliency of 533 Filipino adults who were placed under the nationwide enhanced community quarantine during the COVID-19 pandemic. Butler & Kern's (2016) PERMA Profiler was used to evaluate participants’ wellbeing elements, while Campbell-Sills & Stein's (2007) Connor-Davidson Resiliency Scale -10 was used to measure their resiliency. Collected data were analyzed using regression model and necessary conditions analysis. This study corroborated that all the five pillars of wellbeing are significant positive correlates of resiliency in quarantined adults. Moreover, the results show positively predicts resiliency, while negative emotions negatively predict resiliency. . Lastly, the five pillars of wellbeing are necessary-but-not-sufficient conditions of resiliency. Our results cast a new light on wellbeing elements as constraints rather than enablers of resiliency. This novel result indicates that optimum resiliency is only possible when all of the five pillars of wellbeing are taken care of and when a person is at least minimally contented with their physical health. The present findings underscore the importance of a holistic as against an atomistic approach to maintaining good mental health, which suggest that deficiencies in certain areas of wellbeing may not be fully addressed by overcompensating on other areas, as all five pillars of wellbeing are necessary-but-not-sufficient conditions of resiliency. The study ends with the recommendation for the use of Necessary Conditions Analysis to study both classical and novel psychological research problems.